Editorial: Volatilomics in plant and agricultural research: recent trends - Kasote, Deepak; Lee, Jisun; Sreenivasulu, Nese (Frontiers Media, 2023)
Plants synthesize volatile organic compounds (VOCs) that function as signaling molecules. These VOCs are essential in plant defense against herbivores and insects and play a vital role in plant interaction with biotic and abiotic elements in the environment. Moreover, the composition of VOCs of consumable fruits and grains defines aroma and flavor, thereby considerably deciding consumers’ preferences towards them. In general, the set of biosynthesized volatiles is called volatilome, and analysis of such volatilomes using gas chromatography-mass spectrometry (GC-MS)-based targeted and untargeted approaches is usually referred to as volatilomics. The field of volatilomics is continuously growing and evolving with rapid development in analytical and data processing methods. Hence, capturing recent advances and applications in volatilomics is becoming valuable in advancing interdisciplinary research in plant sciences. The goal of this Research Topic was to collect recent research highlights about the application of volatilomics, both targeted and untargeted in different research areas of plant and agricultural sciences. Under this Research Topic, seven research articles are published that highlight the recent applications of GC-MS-based volatilomics in screening breeding lines/cultivars, understanding the effect of growing conditions on aroma-based fruit quality to optimize quality preferences and unraveling volatiles-based plant-plant communication, including the potential of volatilomics in identifying novel antibacterial and insect repellent volatile compounds